(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2022)
The present article of the research on my scenic experiments, presented in the period of the social isolation of the COVID-19 pandemic, with the use of alternative materials for the creation of lighting, experienced during the period from 2020 to 2022. From which experiments were conducted with light, in the construction of scenes with alternative iluminotechnical materials. The work is a case study, seeking to establish a dialogue with the object light, the actress illuminator (illuminatriz) and the camera. Seeks to create a dialogue with Roberto Gil Camargo, Eduardo Tudella and Fernanda Souza’s styles.